Fast Food/ Slow Food/ The Cultural Economy of the Global Food System - Wilk Richard (Altamira Press, 2006)
This book provides a provocative series of scholarly essays that address some of the myriad issues concerning food and culture in today's world. Introduction, Whole Food Economies: Breaking Down Dichotomies, The Contradiction of Industrial Food, Transforming Markets and Reconnecting with Consumers, Index.